The effects of DS blade׳s geometry features on material׳s creep strength - Xiaojun Yan; Kai Zhang; Ying Deng; Ruijie Sun; Lianshan Lin; Xiaoyong Zhang (Propulsion and Power Research, 2014)
Because of the better creep performance, the directional solidification (DS) Nickel-based turbine blades have been widely used in advanced aero-engines. However, the DS turbine blade׳s different abrupt geometrical changes at different regions cause a variation of temperature field at those regions. Subsequently, the variable temperature field is very likely to lead to a different grain structures at those different region, and those different grain structure finally give rise to a variation in material׳s creep performance at different region in DS turbine blade. To study the variation in creep strength among different regions of a DS turbine blade, this article designed and manufactured three types of DS specimens to simulate the geometry features of platform, shroud and body part of a typical DS turbine blade. Creep tests on these specimens were conducted under the stress level of 608 MPa and temperature of 850 °C, the creep rupture life of platform-like and shroud-like specimens are 93% and 73% of body-like specimens׳ respectively, which support the assumption that there exists a certain variation in material׳s creep strength among different regions in DS turbine blades. The fracture positions of these specimens also support above conclusion. It is suggested that the material׳s creep strength variation among different locations of DS turbine blades should be considered in future turbine blade life design and prediction.